The study of meat quality in Malaysian turkey - N. J. S., Hawa; Idris, Lokman Hakim (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
This study was conducted to investigate the meat quality of Malaysian turkey (Meleagris gallopavo) that have received little attention from the researchers. Malaysian turkey or known as well as ‘Ayam piru’ carcass was subjected to an experiment on meat quality in which involved of carcass composition, pH, color, cooking loss, meat tenderness and proximate analysis. The carcass composition experiment was conducted according to dissection method by using the whole carcass while breast muscle was used for pH, color, cooking loss, muscle tenderness and proximate analysis which include of ash, dry matter, crude protein, crude fibre and fat. At the age of 50 days, 5 carcasses of Malaysian turkey were obtained. Percentage for carcass composition showed that 12.5% was skin and fat, 18.2% was bone and 35.2% was muscle. The pH for meat turkey was 5.6 which slightly acidic. Cooking loss for meat was 10% and colour result showed that L* 57.32 a* 9.09 b* 12.89. Proximate analysis showed that ash content 1.6%, dry matter and moisture 97.2% and 2.7%, crude fat 11.6%, crude fibre 10% and crude protein was 23%.